Detecting and staging podoconiosis cases in North West Cameroon: positive predictive value of clinical screening of patients by community health workers and researchers. (December 2016) - Wanji, Samuel; Kengne-Ouafo, Jonas; Datchoua-Poutcheu, Fabrice; Njouendou, Abdel; Tayong, Dizzel; Sofeu-Feugaing, David; Amvongo-Adjia, Nathalie; Fovennso, Bridget; Longang-Tchounkeu, Yolande; Tekola-Ayele, Fasil; Enyong, Peter; Newport, Melanie; et al.
Abstract Background The suitability of using clinical assessment to identify patients with podoconiosis in endemic communities has previously been demonstrated. In this study, we explored the feasibility and accuracy of using Community Health Implementers (CHIs) for the large scale clinical screening of the population for podoconiosis in North-west Cameroon. Methods Before a regional podoconiosis mapping, 193 CHIs and 50 health personnel selected from 6 health districts were trained in the clinical diagnosis of the disease. After training, CHIs undertook community screening for podoconiosis patients under health personnel supervision. Identified cases were later re-examined by a research team with experience in the clinical identification of podoconiosis. Results Cases were identified by CHIs with an overall positive predictive value (PPV) of 48.5% [34.1–70%]. They were more accurate in detecting advanced stages of the disease compared to early stages; OR 2.07, 95% CI = 1.15–3.73, p  = 0.015 for all advanced stages). Accuracy of detecting cases showed statistically significant differences among health districts (χ2 = 25.30, p  = 0.0001). Conclusion Podoconiosis being a stigmatized disease, the use of CHIs who are familiar to the community appears appropriate for identifying cases through clinical diagnosis. However, to improve their effectiveness and accuracy, more training, supervision and support are required. More emphasis must be given in identifying early clinical stages and in health districts with relatively lower PPVs.